Report on the comparison of the realisations of the ITS-90 over the range 234.315 6 K to 933.473 K between Centro Español de Metrología (CEM) and Instituto Nacional de Metrología (SIM.T-K9.2) - Campo, Dolores del; Gómez, Elena; Sánchez, Ciro Alberto; Méndez-Lango, Edgar; Andrés Carvajal, Sergio; Bohórquez, Andrés Jhovanny; Bohórquez Garzón, Andrés Jhovanny; Sánchez Morales, Ciro Alberto (IOP Publishing, 2022)
Main text The comparison of the realization of the International Temperature Scale of 1990 (ITS- 90) over the range 234,315 6 K (triple point of mercury) to 993,473 K (freezing point of aluminium) in the National Metrology Institutes of Spain (Centro Español de Metrología - CEM) and Colombia (Instituto Nacional de Metrología - INM) has been organized with the aim to provide support to the Calibration Measurement Capabilities claimed by INM in this range. Due to the participation of CEM in the regional comparison EUROMET.T-K9, the linkage with the corresponding key comparison, CCT-K9, is possible. The measurements of this comparison were performed during September 2018 and June 2020. To reach the main text of this paper, click on Final Report. Note that this text is that which appears in Appendix B of the BIPM key comparison database https://www.bipm.org/kcdb/. The final report has been peer-reviewed and approved for publication by the CCT, according to the provisions of the CIPM Mutual Recognition Arrangement (CIPM MRA).